Assessment of Depression among Adolescent Students of Government Medical and Engineering Colleges, Hassan, Karnataka - Subhashini KJ; Praveen G; Sundar M (National Journal of Community Medicine, 2018)
Background: Depression is the leading cause of disability worldwide. An estimated 20% of the world’s adolescents report a lifetime prevalence of depression. Especially Students of professional courses are under stress, owing to ever-increasing study load and expectations from the society that they fall into depression. If adolescents with mental health problems get the care they need, they can avoid suffering throughout life. Objectives: To assess the magnitude of depression among adolescent students of Government Medical and Engineering colleges, Hassan, Karnataka and its association with the psycho-social factors. Methods: A Descriptive questionnaire-based study was conducted among adolescent students of Hassan Institute of Medical Sciences (Government Medical College) and Government Engineering College. Depression was assessed using Beck’s Depression Inventory-II and psychological wellbeing and stress were measured using General Health Questionnaire-12. Results: Of the total 150 Medical and 150 Engineering students, 22% of Medical and 35.3% of Engineering students were found to be depressed and 65.3% of Medical and 57.33% of Engineering students were found to be in distress. Statistically significant association was found between psycho-social factors and depression. Conclusion: Mental health issues have to be identified and addressed in the Professional colleges by providing them counselling, stress management training and moral support so that the potential of the students is optimized to the fullest.